The effectiveness of the modified type of module in the teaching of social studies at Maryknoll College Grade School - Cunanan, Gloria S. 1954- (College of Education, University of the Philippines Diliman, 1979)
The study aimed to find out whether the adoption of a modified type of module in the teaching of social studies at Maryknoll College Grade School in Quezon City for the year school 1977-1978 should be continued or not. Data collection was done using a questionnaire and observations. The questionnaire was administered to 168 average students from Grades 3-6 towards the end of school year 1977-1978. It was revealed that ratings on the basic components of the module centered mostly under the headings as a little bit hard and fair while the overall effectiveness of the module went under very helpful and helpful. The use of Filipino as the medium of instruction also deterred the comprehension of the students of the said module. The module was proven effective in achieving the objectives of the Social Studies program.